Hubungan antara Pola Asuh Orang Tua yang Bekerja dengan Perkembangan Sosial Emosional Anak Prasekolah - Yuliana, Sela Tri; Maulidia, Rahmawati; Trigantara, Regista (Jurnal Gema Keperawatan, 2025)
The decision of both parents to work leads to limited interaction time with their child, which in turn can affect parenting styles. This situation may impact the social and emotional development of preschool children, as in this condition, children greatly need attention from their parents, especially to support their social and emotional growth. The purpose of this study is to understand the relationship between the parenting styles of working parents and the social and emotional development of preschool children at TK Muslimat NU 2 Nasihudin Gunungronggo, Malang Regency. The method used in this study is a correlational quantitative research design with a cross-sectional approach. The number of respondents in this study was 64, divided into classes A and B using proportionate stratified random sampling techniques. The Parenting Style Dimensions Questionnaire (PSDQ) and the Age and Stage Questionnaire: Social-Emotional Second Edition (ASQ:SE-2) were used as instruments in this study. Data analysis in this study employed the Spearman Rank test. The results of the data analysis in this study showed a correlation between the two variables with a p-value of (0,000) (0,05) and a correlation coefficient of 0,703, indicating a strong positive correlation between the parenting styles of working parents and the social-emotional development of preschool children. Democratic parenting can be used to optimize the social-emotional development of children. One of the aspects influencing the application of parenting styles is the busyness of the parents at work. Parenting styles will affect the child's development according to the approach used, and this will impact the social-emotional development of preschool children.